Media Literacy: Smart In Educating Society In Information Technology Era - Darwadi MS (Intelektual Pustaka Media Utama, 2017)
Communication Media has been developed in the form of printed Media and electronic Media. This development is not only easy to communicate and receive information fast wherever and whenever we go but also cheap. Besides positive impacts, it has negative influence to children and teenagers growth and adults. In other word it brings great influence to people. That is why Media literacy is needed so people will be able to know what Media is. Media presents through a long process. What we see is not 100% true. There are politics, economics, culture etc in it. People have to know and understand Media. So, media literacy is so important to educate society when they access information in mass media. The program must be doing together, comprehensive from all element in society in structural and cultural way.